Diel change in inorganic nitrogenous nutrient dynamics and associated oxygen stoichiometry along the Pearl River Estuary. (15th August 2022) - Xu, Min Nina; Wu, Yanhua; Zhang, Xiao; Tang, Jin-Ming; Tan, Ehui; Zheng, Zhen-Zhen; Du, Moge; Yan, Xiuli; Kao, Shuh-Ji
Highlights: NH4 + -consuming hotpots and NO3 − -consuming hotpots decoupled in space in estuary. NO3 − /NO2 − behave conservatively due to the high preference on NH4 + for phytoplankton. Upstream NH4 + turned into organics or NO3 − in 2 days to affect microbial niches offshore. Counterintuitively, high NH4 + input may lead to net O2 production through diel N-dynamics. Abstract: The reactive nitrogen (N) emitted from continents significantly perturbs the pristine N cycle around the land-ocean boundary resulting in eutrophication and hypoxia. As nutrients are transported downstream through an estuary, various types of biological processes co-occur to modulate nitrogen speciation to influence the biogeochemical habitats for downstream microorganisms. We surveyed the Pearl River Estuary to examine the N transfer dynamics among nitrogen species with considering process-specific oxygen production and consumption. By using 15 N pulse-tracing techniques, we measured ammonia oxidation and uptakes of ammonium, nitrite, and nitrate simultaneously under dark and light conditions in parallel. Light strongly inhibited nitrification but enhanced N uptake, and such light effect was further considered in the calculation for nitrogen transformation rates over a diel cycle. We found both oxidation and uptake of ammonium decreased seaward as substrate decreased. The nitrifier and phytoplankton work in antiphase to draw down incoming ammonium rapidly. Contrary to ammonium uptake, uptake of nitrite and nitrate showed a seaward increasing pattern. Such an inverse spatial pattern implies a shift in N preference for phytoplankton. Such high ammonium preference inhibits nitrate/nitrite uptake allowing them to behave conservatively in the estuary and to travel farther to outer estuary. By integrating oxygen consumption and production induced by N transformation processes over the diel cycle, oxygen was produced although allochthonous ammonium input is high (∼250 μM). For most stations, ammonium was completely consumed within 2 days, some stations even less than 0.5 days, implying that although the water residence time is short (2-15 days), tremendous input of ammonium N from upstream was transformed into particulate organic or nitrate forms during traveling to modulate the biogeochemical niche, including substrate, organics and oxygen, of coastal microbes in water column and sediments.